The influence of exogenous methyl jasmonate on the structure and physicochemical properties of wheat starch under cadmium stress - Wang, Hairong; Zhang, Dazhong; Meng, Liwen; Yang, Fujing; Sun, Zhiwei; Li, Yilong; Ding, Qin; Niu, Na; Ma, Lingjian (Frontiers in Plant Science, 2025)
IntroductionMeJA enhances Cd stress resistance and reduces Cd accumulation in wheat (Triticum aestivum L.). Our previous study demonstrated that exogenous MeJA regulated wheat responses to Cd stress in a concentration-dependent manner. Building on this, the present study investigated the effects of MeJA spraying on grain weight and starch physicochemical properties in wheat under Cd stress.MethodsWheat plants were exposed to different soil Cd concentrations (0, 5, 50 mg/kg) and treated with foliar sprays of MeJA at varying concentrations (0, 1 and 10 µM).ResultsCd stress significantly reduced grain weight, inhibited starch synthesis, and impaired starch physicochemical properties by decreasing crystallinity, gelatinization enthalpy, and freeze-thaw stability. In contrast, low-concentration MeJA (1 µM) significantly increased thousand-grain weight, total starch content, and B-type starch granule content, while improving starch crystalline structure, thermal stability, and functional properties, thereby alleviating Cd-induced damage. Genotypic variation revealed a MeJA-mediated trade-off between stress defense and developmental metabolism, with the Cd-tolerant cultivar exhibiting a more efficient jasmonate signaling and metabolic compensation mechanism.DiscussionThis study extends previous physiological findings to the starch quality level and provides new mechanistic insight into MeJA-mediated regulation of grain quality and stress adaptation in wheat grown under Cd-contaminated conditions.